The Complement System in Flavivirus Infections - Conde, Jonas N.; Silva, Emiliana M.; Barbosa, Angela S.; Mohana-Borges, Ronaldo (Frontiers in Microbiology, 2017)
The incidence of flavivirus infections has increased dramatically in recent decades in tropical and sub-tropical climates worldwide, affecting hundreds of millions of people each year. The Flaviviridae family includes dengue, West Nile, Zika, Japanese encephalitis, and yellow fever viruses that are typically transmitted by mosquitoes or ticks, and cause a wide range of symptoms, such as fever, shock, meningitis, paralysis, birth defects, and death. The flavivirus genome is composed of a single positive-sense RNA molecule encoding a single viral polyprotein. This polyprotein is further processed by viral and host proteases into three structural proteins (C, prM/M, E) and seven non-structural proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B, NS5) that are involved in viral replication and pathogenicity. The complement system has been described to play an important role in flavivirus infection either by protecting the host and/or by influencing disease pathogenesis. In this mini-review, we will explore the role of complement system inhibition and/or activation against infection by the Flavivirus genus, with an emphasis on dengue and West Nile viruses.